2017
DOI: 10.1002/ajim.22694
|View full text |Cite
|
Sign up to set email alerts
|

Baby boomers in the United States: Factors associated with working longer and delaying retirement

Abstract: Baby boomers expect to work longer than their predecessors. Efforts to improve work quality and availability for older workers are urgently needed, particularly in physically demanding occupations. Am. J. Ind. Med. 60:315-328, 2017. © 2017 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…By using the surveys as an integrated dataset, the difficulty of heterogeneity associated with individual patient data analysis is minimised. This study has also been conducted in the over 50-year age group, a relatively understudied group in terms of the examination of health and work and the contribution of health in the transition to work disability 17. Furthermore, the consistent measures included in each of the surveys enabled the findings to be adjusted for age, gender and social class, each of which is known to be associated with work disability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By using the surveys as an integrated dataset, the difficulty of heterogeneity associated with individual patient data analysis is minimised. This study has also been conducted in the over 50-year age group, a relatively understudied group in terms of the examination of health and work and the contribution of health in the transition to work disability 17. Furthermore, the consistent measures included in each of the surveys enabled the findings to be adjusted for age, gender and social class, each of which is known to be associated with work disability.…”
Section: Discussionmentioning
confidence: 99%
“…Musculoskeletal pain and depression commonly coexist,14 and having comorbidities is associated with longer sick leave and increased work disability 15. There is some suggestion that these associations may change over time,16 and with increasing retirement age and a projected increase in the number of workers delaying retirement due to shrinking retirement resources,17 it is important to examine the impact of the most common conditions in relation to a worker’s ability to maintain employment and to identify the direction and extent of any such trends that are occurring.…”
Section: Introductionmentioning
confidence: 99%
“…This places more onus on Millennials to plan for retirement, yet Millennials prefer a higher salary and weaker retirement benefits while Baby Boomers prefer a lower salary and stronger retirement benefits (Wells Fargo, 2016 ). Despite that preference for stronger retirement benefits, Baby Boomers also expect to continue working past Social Security retirement benefit eligibility (Dong et al, 2017 ). Generation Xers and younger Baby Boomers have a similar risk of being unable to smooth consumption in retirement at 57% and 50%, respectively, while older Baby Boomers have a 37% risk (Munnell et al, 2006 ).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Studies that use the Medicaid expansion and employer coverage mandate, also find no effect on labor force participation (Gooptu, Moriya, Simon, & Sommers, 2016;Kaestner, Garrett, Chen, Gangopadhyaya, & Fleming, 2017;Leung & Mas, 2016;Moriya, Selden, & Simon, 2016). Dong, Wang, Ringen, and Sokas (2017), found that newer retirees are expecting to work longer than previous generations. However, other studies find that the ACA had little to no significant impact on those retirement decisions (Ayyagari, 2017;French, von Gaudecker, & Jones, 2016;Gustman, Steinmeier, & Tabatabai, 2016;Kaestner et al, 2017;Levy, Buchmueller, & Nikpay, 2016).…”
Section: Introductionmentioning
confidence: 99%